Elevated FiO(2) increases SARS-CoV-2 co-receptor expression in respiratory tract epithelium - Myti, Despoina (Am J Physiol Lung Cell Mol Physiol, 2020)
The severity of coronavirus disease 2019 (COVID-19) is linked to an increasing number of risk factors, including exogenous (environmental) stimuli such as air pollution, nicotine, and cigarette smoke. These three factors increase the expression of angiotensin I converting enzyme 2 (ACE2), a key receptor involved in the entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)—the etiological agent of COVID-19—into respiratory tract epithelial cells. Patients with severe COVID-19 are managed with oxygen support, as are at-risk individuals with chronic lung disease. To date, no study has examined whether an increased fraction of inspired oxygen (FiO(2)) may affect the expression of SARS-CoV-2 entry receptors and co-receptors, including ACE2 and the transmembrane serine proteases TMPRSS1, TMPRSS2, and TMPRSS11D. To address this, steady-state mRNA levels for genes encoding these SARS-CoV-2 receptors were assessed in the lungs of mouse pups chronically exposed to elevated FiO(2), and in the lungs of preterm-born human infants chronically managed with an elevated FiO(2). These two scenarios served as models of chronic elevated FiO(2) exposure. Additionally, SARS-CoV-2 receptor expression was assessed in primary human nasal, tracheal, esophageal, bronchial, and alveolar epithelial cells, as well as primary mouse alveolar type II cells exposed to elevated oxygen concentrations. While gene expression of ACE2 was unaffected, gene and protein expression of TMPRSS11D was consistently upregulated by exposure to an elevated FiO(2). These data highlight the need for further studies that examine the relative contribution of the various viral co-receptors on the infection cycle, and point to oxygen supplementation as a potential risk factor for COVID-19.